Biomarkers for brain injury and copper toxicity in Wilson's disease: a diffusion tensor imaging study. Issue 6 (27th May 2022) - Shribman, Samuel; Bocchetta, Martina; Burrows, Maggie; Gillett, Godfrey T; Tsochatzis, Emmanuel; Bandmann, Oliver; Rohrer, Jonathan D; Warner, Thomas T
Abstract : Introduction: Chelation therapy is used to 'de-copper' patients with Wilson's disease but neurological outcomes are unpredictable and biomarkers of end-organ damage are needed. Methods: We prospectively performed clinical assessments, venepuncture and 3T MRI in 40 patients with Wilson's disease. Using tract-based spatial statistics, we compared diffusion tensor imaging parameters across white matter tracts between patients with neurological (n=23) and hepatic (n=17) presentations and active (n=5) and stable (n=35) disease. We also tested associations with neurological examination scores and serum free copper concentrations in stable patients. Results: There were no differences in DTI parameters between patients with neurological and hepatic presentations, however examination scores were negatively associated with axial diffusivity in subcortical tracts in stable patients. Patients with active disease had widespread increases in mean, axial and, to a lesser extent, radial diffusivity. In contrast, increasing serum copper concentrations in stable patients were associated with widespread increases in mean, radial and, to a lesser extent, axial diffusivity. Conclusions: We demonstrate that distinct patterns of abnormal white matter diffusivity are associated with brain injury and copper toxicity in Wilson's disease. Decreases in axial diffusivity in chronically-treated patients likely reflect axonal loss. Increases in axial and radial diffusivity are a promising biomarker for monitoring treatment response. s.shribman@ucl.ac.uk